Kearifan Lokal Dalam Mitigasi Bencana Banjir Berulang Yang Terjadi di Kecamatan Karanganyar Demak Tahun 2024 - Clara Hilaria Valentina Saputra; Neny Marlina (Journal of Politic and Government Studies, 2026)
This study examines the recurring floods that occurred in Karanganyar District, Demak Regency, in 2024, specifically in Ketanjung Dukuh Norowito Village. This study demonstrates the need for disaster mitigation efforts that focus not only on structural approaches but also accommodate the local wisdom of the community. This study aims to analyze the role of local wisdom as a social phenomenon that supports mitigation decision-making and its success, and to determine whether the government's response to recurrent flooding is beneficial for mitigation. The researchers also examine whether the